Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(P=\sqrt{\left(x-1\right)+2\sqrt{x-1}+1}+\sqrt{\left(x-1\right)-2\sqrt{x-1}+1}\)
\(P=\sqrt{\left(\sqrt{x-1}+1\right)^2}+\sqrt{\left(\sqrt{x-1}-1\right)^2}\)
\(P=\left|\sqrt{x-1}+1\right|+\left|\sqrt{x-1}-1\right|\)
\(\Rightarrow P=\sqrt{x-1}+1+\sqrt{x-1}-1
\left(x\ge2\right)\) hoặc \(P=\sqrt{x-1}+1-\sqrt{x-1}+1\left(1\le x\le2\right)\)
\(\Rightarrow P=2\sqrt{x-1}
\left(x\ge2\right)\) hoặc \(P=2
\left(1\le x\le2\right)\)
a/ Ta có
P = \(\frac{1+\sqrt{x}}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}\) - \(\frac{2+x}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}\) - \(\frac{1+\sqrt{x}}{x+\sqrt{x}+1}\)
= \(\frac{-\sqrt{x}}{1+\sqrt{x}+x}\)
b: \(=\dfrac{\sqrt{14+6\sqrt{5}}+\sqrt{14-6\sqrt{5}}}{\sqrt{2}}=\dfrac{3+\sqrt{5}+3-\sqrt{5}}{2}=\dfrac{6}{\sqrt{2}}=3\sqrt{2}\)
c: \(=\sqrt{x-1}+1+\sqrt{x-1}-1=2\sqrt{x-1}\)
\(\sqrt{x+2\sqrt{x-1}}+\sqrt{x-2\sqrt{x-1}}\)
\(\sqrt{x-1+2\sqrt{x-1}+1}+\sqrt{x-1-2\sqrt{x-1}+1}\)
\(\sqrt{\left(\sqrt{x-1}+1\right)^2}+\sqrt{\left(\sqrt{x-1}-1\right)^2}\)
\(\left|\sqrt{x-1}+1\right|+\left|\sqrt{x-1}-1\right|\)
\(TH1:1\le x\le2\)
\(\sqrt{x-1}+1+1-\sqrt{x-1}\)
\(=2\)
\(TH2:x>2\)
\(\sqrt{x-1}+1+\sqrt{x-1}-1\)
\(2\sqrt{x-1}\)
ĐK : x >= 1
Đặt \(A=\sqrt{x+2\sqrt{x-1}}+\sqrt{x-2\sqrt{x-1}}\)
\(A^2=\left(\sqrt{x+2\sqrt{x-1}}+\sqrt{x-2\sqrt{x-1}}\right)^2\)
\(A^2=\left|x+2\sqrt{x-1}\right|+2\sqrt{\left(x+2\sqrt{x-1}\right)\left(x-2\sqrt{x-1}\right)}+\left|x-2\sqrt{x-1}\right|\)
\(A^2=x+2\sqrt{x-1}+2\sqrt{x^2-4x+4}+x-2\sqrt{x-1}\)
\(A^2=2x+2\sqrt{\left(x-2\right)^2}=2x+2\left|x-2\right|\)
Với 1 ≤ x < 2 => A2 = 2x - 2( x - 2 ) = 2x - 2x + 4 = 4 => A = 2
Với x ≥ 2 => A2 = 2x + 2x - 4 = 4x - 4 => A = 2√(x-1)